Consumer Awareness and Consumer Protection in Hungary - Szucs, Robert Sandor (European Scientific Journal, ESJ, 2018)
The consumer asserts that his decisions are consistent and rational. He likes to believe this about himself. Based on previous surveys it can be stated that our confidence persists until the assessment of the actual level of our knowledge on consumer protection takes place, e.g. in the form of a test containing 13 substantial questions to measure the actual level of knowledge. This test was filled out by 2182 persons over 18 years of age. In overall, we can say that no matter how much we love to think about ourselves as being conscious customers, this statement is generally not true. The level of consumer protection knowledge is generally insufficient in Hungary. Only 13% of consumers have the right to say that they are knowledgeable of consumer protection at average level, while the good level was achieved only by 2.1% of the respondents.